2019
DOI: 10.1152/ajpheart.00094.2018
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection via the skin: nociceptor-induced conditioning against cardiac MI in the NIC of time

Abstract: Timely reperfusion is still the most effective approach to limit infarct size in humans. Yet, despite advances in care and reduction in door-to-balloon times, nearly 25% of patients develop heart failure postmyocardial infarction, with its attendant morbidity and mortality. We previously showed that cardioprotection results from a skin incision through the umbilicus in a murine model of myocardial infarction. In the present study, we show that an electrical stimulus or topical capsaicin applied to the skin in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 62 publications
0
14
0
6
Order By: Relevance
“…Adult male Trpv1 −/− (B6.129× 1-Trpv1 tm1Jul /J) mice (1.5–2 months old, n = 18) were obtained from The Jackson Laboratory (Bar Harbor, ME, USA), while the appropriate WT background strain C57Bl/6 mice were purchased from Charles River Laboratories (male, 1.5–2 months old, n = 18, Wilmington, MA, USA). The Trpv1 −/− mice have a targeted mutation causing a non-functional truncated form of TRPV1 (Caterina et al, 2000 ; Ren et al, 2019 ; Stanford et al, 2019 ). Mice were maintained in 12 h light/dark cycles, and animals were allowed water and standard rodent chow as desired.…”
Section: Methodsmentioning
confidence: 99%
“…Adult male Trpv1 −/− (B6.129× 1-Trpv1 tm1Jul /J) mice (1.5–2 months old, n = 18) were obtained from The Jackson Laboratory (Bar Harbor, ME, USA), while the appropriate WT background strain C57Bl/6 mice were purchased from Charles River Laboratories (male, 1.5–2 months old, n = 18, Wilmington, MA, USA). The Trpv1 −/− mice have a targeted mutation causing a non-functional truncated form of TRPV1 (Caterina et al, 2000 ; Ren et al, 2019 ; Stanford et al, 2019 ). Mice were maintained in 12 h light/dark cycles, and animals were allowed water and standard rodent chow as desired.…”
Section: Methodsmentioning
confidence: 99%
“…The mutant forward primer was TAA AGC GCA TGC TCC AGA CT compared with the WT forward primer of TGG CTC ATA TTT GCC TTC AG. The common primer was CAG CCC TAG GAG TTG ATG GA. DNA gel electrophoresis of Trpv1 −/− animals showed a single band at 176 bp, indicative of truncated TRPV1 (Caterina et al, 2000;Ren et al, 2019;Stanford et al, 2019), whereas WT showed a single band at 289 bp indicative of the native protein. We verified this pattern in each animal utilized.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Adult male Trpv1 −/− (B6.129 × 1-Trpv1 TM1Jul /J) mice (1.5-2 months old) were obtained from The Jackson Laboratory, whereas the appropriate wild-type (WT) background strain C57Bl/6 mice were purchased from Charles River Laboratories (male, 1.5-2 months old). The Trpv1 −/− mice have a targeted mutation causing a non-functional truncated form of TRPV1 (Caterina et al, 2000;Ren et al, 2019;Stanford et al, 2019). Trpv1 −/− animals were genotyped prior to performing experiments, following our protocol (Ward et al, 2014;Weitlauf et al, 2014;Sappington et al, 2015) using primers recommended by the vendor.…”
Section: Animal Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, pathway analysis showed that the altered metabolites and proteins were related to neuroactive ligand-receptor interaction. Previous research indicated that the nervous system, including the sympathetic system and the parasympathetic system, regulates cardiac activity regardless of the heart's physiological condition [43,44]. In addition, researchers have reported that the cardio protection effects of sevoflurane is associated with neuroactive ligandreceptor interaction in patients undergoing coronary artery bypass graft surgery [45].…”
Section: Plos Onementioning
confidence: 99%